Pengembangan Skala Efikasi Diri Guru Bimbingan Dan Konseling Abad-21 - Pravesti, Cindy Asli; Mufidah, Elia Firda; Nurlitasani, Eva Nanda; Utari, Elly Dwi Putri (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
In facing the new changes of the 21st century, guidance and counseling teachers need self-efficacy in working with clients. This is intended to carry out the process of providing guidance and counseling services. The aim is to determine the measure of self-efficacy of 21st century guidance and counseling teachers based on the aspects developed. The research method used is the 4D development model (define, design, develop, disseminate). The sample used was 117 guidance and counseling teachers. Meanwhile, data analysis was carried out through expert tests by 2 people with inter-rater agreement and content analysis. The results show that the self-efficacy scale for 21st century guidance and counseling teachers is quite feasible and quite reliable. Therefore, these results provide an understanding that guidance and counseling teachers in the 21st century must have self-efficacy in order to have a positive impact on counselees. For this reason, it is important for guidance and counseling teachers to have self-confidence in the 21st century in order to understand their role as guidance and counseling teachers or counselors. Thus, the self-efficacy of 21st century guidance and counseling teachers will be optimal.